Review study on early recognition of symptoms and parental care for autism spectrum disorders children - Vidya, Bhagat; San Thitsa, Aung; Nordin, Simbak (2019)
In the current decade, the multidisciplinary approach is popularizing for the treatment of Autism Spectrum Disorders. The early recognition of symptoms and parental care is necessary for a good prognosis. Though the availability of clinical services for children and adolescents with autism spectrum disorder (ASD) and other developmental disorders, and their families are in reach, delayed recognition of the symptoms by parents leads to poor prognosis. The study aims at throwing light on significance of early recognition of symptoms and parental care for autism spectrum disorders children. This literature review was completed using electronic databases. The study had analyzed 30 articles from the years 19 to 2018. The reviewed articles were on autism, autism spectrum disorder, and early recognition of symptoms, prevalence, and parent’s awareness. The current study concludes conceptualizing and understanding the significance of early recognition of symptoms, parent’s awareness of recent advances in ASD treatment, multidisciplinary approaches, and their motivation.